Pro-Inflammatory and Diagnostic Roles of Serum Amyloid A and C-reactive protein in Schizophrenia (African Journal of Biomedical Research, 2023)
Schizophrenia is a chronic and severe disorder of the mind which affects a person's way of thinking, acting, expressing emotions, perceiving reality, and being related to others. C-reactive protein (CRP) and Serum Amyloid A (SAA) are acute-phase proteins that play critical roles in inflammatory processes and the body's response to infection. SAA is an apolipoprotein in the body that is linked to high-density lipoprotein (HDL). This study looks at the pro-inflammatory role of CRP and SAA as acute-phase protein biomarkers in schizophrenia patients. A total of 70 subjects participated in this study, including 40 schizophrenic patients and 30 apparently healthy individuals with no symptoms of schizophrenia. Serum level of lipid profile was determined using standard spectrophotometric method while SAA and CRP were determined using enzyme-linked immune sorbent assay (ELISA). In schizophrenic subjects, mean total cholesterol (TCHOL), triglyceride (TRIG), HDL, SAA, and CRP levels were significantly higher (p